From pullout-techniques to modular elastic stable chest repair: the evolution of an open technique in the correction of pectus excavatum - Schulz-Drost, Stefan; Syed, Julia; Luber, Anna-Maria; Carbon, Roman T.; Besendörfer, Manuel (Journal of Thoracic Disease, 2019)
Background: Traditionally open procedures have been replaced by minimally invasive techniques in the correction of pectus excavatum. Efforts to improve the extent of mobilization of the chest wall and its stabilization have led to constant modifications. There is currently no consensus about the best procedure for correction of pectus excavatum. Methods: Based on the contributions of a single institution for the last 60 years, we present the various strategies used for the correction of pectus excavatum and the evolution of operational procedures. These approaches are compared with those performed internationally at similar periods. Results: Resections with external extension achieved moderate results and were modified in 1962 to the “Shred” method. The establishment of the “Strut” method in 1963 and, in 1977, its extension with the erection of the lower rib arches significantly improved patient outcomes. The “minimization” of the procedure in 2006 was accompanied by an increase in wound healing disorders and recurrent deformities. Since 2010, elastic stable chest repair (ESCR) has provided lossless mobilization and sternal elevation for healing costosternal pseudarthrosis and allowed correction of complex recurrences with excellent cosmetic-functional results. Strong asymmetric or broad-base deformities can now be stabilized using a modular hybrid technique of transsternal bar and locked plates. Conclusions: ESCR marks the end of the 60-year development of an open procedure and, after loss-free mobilization of the chest wall by elastic-stable biomechanical management, optimizes the possibility of anatomical reconstruction of the chest wall during initial and re-interventions, achieving a permanent, physiologically stable remodeling of the chest wall.